Spatial congregation of STAT binding directs selective nuclear architecture during T-cell functional differentiation - Hakim, Ofir; Sung, Myong-Hee; Nakayamada, Shingo; Voss, Ty C.; Baek, Songjoon; Hager, Gordon L. (Genome Research, 2012)
Higher-order genome organization shows tissue-specific patterns. However, functional relevance and the mechanisms shaping the genome architecture are poorly understood. Here we report a profound shift from promiscuous to highly selective genome organization that accompanies the effector lineage choice of differentiating T cells. As multipotent naive cells receive antigenic signals and commit to a T helper (Th) pathway, the genome-wide contacts of a lineage-specific cytokine locus are preferentially enriched for functionally relevant genes. Despite the establishment of divergent interactomes and global reprogramming of transcription in Th1 versus Th2, the overall expression status of the contact genes is surprisingly similar between the two lineages. Importantly, during differentiation, the genomic contacts are retained and strengthened precisely at DNA binding sites of the specific lineage-determining STAT transcription factor. In cells from the specific STAT knock-out mouse, the signature cytokine locus is unable to shed the promiscuous contacts established in the naive T cells, indicating the importance of genomic STAT binding. Altogether, the global aggregation of STAT binding loci from genic and nongenic regions highlights a new role for differentiation-promoting transcription factors in direct specification of higher-order nuclear architecture through interacting with regulatory regions. Such subnuclear environments have significant implications for efficient functioning of the mature effector lymphocytes.
10.1101/gr.147652.112